Indigenous Sky Stories: Reframing How we Introduce Primary School Students to Astronomy — a Type II Case Study of Implementation - Ruddell, Nicholas; Danaia, Lena; McKinnon, David (The Australian Journal of Indigenous Education, 2016)
The Indigenous Sky Stories Program may have the potential to deliver significant and long-lasting changes to the way science is taught to Year 5 and 6 primary school students. The context for this article is informed by research that shows that educational outcomes can be strengthened when Indigenous knowledge is given the space to co-exist with the hegemony of current western science concepts. This research presents a case study of one primary school involved in the Indigenous Sky Stories Program. It showcases how teachers and students worked in conjunction with their local community to implement the program. The results suggest that introducing cultural sky stories into the science program, engaged and primed Year 5 and 6 students to seek out additional sky stories and to investigate the astronomical content mapped to the National Science Curriculum. The involvement of Aboriginal elders and community enriched the experience for all involved. The integrated science program appears to generate positive engagement for both Indigenous students and their non-Indigenous peers. Additionally, the program provided a valuable template for teachers to emulate and which can act as a model for the requirement to include Indigenous perspectives in the new National Science Curriculum.